Pengaruh Rasio Pasar, Rasio Solvabilitas, dan Rasio Profitabilitas Terhadap Harga Saham Sebelum dan Selama Pandemi Covid-19 - Alhamzah, Anya Sendy Aprista; Moeljadi, Moeljadi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The Covid-19 pandemic has affected the economic growth of various company sectors in Indonesia. The restriction on people’s activity to prevent the spread of the disease has caused the drop of domestic companies’ financial performance and stock price. This research was conducted to identify the companies’ financial performance by analyzing their financial reports using financial ratios. The better their financial performance, the more likely investors invest in them. The objective of this research is to identify the effects of Earnings per Share (EPS), Debt-to-Equity Ratio (DER), Net Profit Margin (NPM), and Return on Assets (ROA) on the stock prices before and during the Covid-19 pandemic. The sample of this quantitative explanatory research is nine pharmaceutical and health research sub-sector companies listed on the Indonesia Stock Exchange. A Multiple linear regression analysis was performed on the secondary data, i.e., the semiannual financial reports published in the investment gallery of the Indonesia Stock Exchange, in IBM SPSS version 29.0. This study finds that EPS before the pandemic has no significant effect, that EPS during the pandemic have positive and significant effect, that DER and NPM before the pandemic has positive and significant effects, that DER and NPM during the pandemic have significant and negative effects, and that ROA has no significant effect both before and during the pandemic. In this research investors saw EPS, DER, and NPM as main components for their investment decision making but did not consider ROA since it did not directly affect dividend or capital gain that they have expected. Abstrak Pandemi COVID-19 membawa dampak pada pertumbuhan ekonomi berbagai sektor perusahaan di Indonesia. Aktivitas masyarakat dibatasi untuk mencegah penyebaran virus COVID-19 menyebabkan turunnya kinerja keuangan serta harga saham perusahaan-perusahaan dalam negri. Penelitian ini bertujuan untuk mengetahui pengaruh Earning per Share, Debt to Equity Ratio, Net Profit Margin, dan Return on Assets terhadap Harga Saham sebelum dan selama pandemi COVID-19. Jenis penelitian ini adalah penelitian eksplanatori dengan pendekatan kuantitatif. Sampel dalam penelitian ini adalah 9 perusahaan subsektor Farmasi dan Riset Kesehatan yang terdaftar di Bursa Efek Indonesia. Penelitian ini menggunakan data sekunder berupa laporan keuangan semester perusahaan. Pengujian dalam penelitian ini menggunakan analisisi regresi linier berganda. Hasil yang diperoleh yaitu EPS sebelum pandemi tidak berpengaruh signifikan, EPS selama pandemi berpengaruh signifikan positif, DER dan NPM sebelum pandemi berpengaruh signifikan positif, DER dan NPM selama pandemi berpengaruh signifikan negatif, ROA sebelum dan selama pandemi tidak berpengaruh signifikan. Pada penelitian ini investor memperhatikan EPS, DER, dan NPM sebagai komponen utama dalam pengambilan keputusan investasi, namun tidak melihat ROA karena ROA tidak berdampak langsung pada Deviden atau Capital Gain yang diharapkan Investor.